2008
DOI: 10.1080/10584580802541080
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Magnetoelectric Effect of Three-Phase Multiferroic Particulate Composites

Abstract: Using the effective medium approximation, we set up a model for the investigation of 3-phase magnetoelectric composites of 0-0-3 connectivity. The two particulate phases are magnetostrictive particles and piezoelectric particles, which are considered to be spherical in shape and dispersed in a continuous polymer matrix of non-negligible electrical conductivity. The electric, magnetic and elastic properties of the constituents are assumed to be isotropic. We calculate the magnetoelectric voltage/charge coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The model showed that these coefficients depended on the sum of the in-plane piezomagnetic strains, ε 11 +ε 22 , which in turn depended strongly on the orientation of the applied magnetic fields relative to the laminate's interface. Tsang et al [29] developed an effective medium-based micromechanical model for 3-phase magnetoelectric composites consisting of spherical magnetostrictive and piezoelectric particles embedded in a conductive polymer matrix. Based on their model, the authors calculated the magnetoelectric charge and voltage coefficients, and the results agreed reasonably well with corresponding experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The model showed that these coefficients depended on the sum of the in-plane piezomagnetic strains, ε 11 +ε 22 , which in turn depended strongly on the orientation of the applied magnetic fields relative to the laminate's interface. Tsang et al [29] developed an effective medium-based micromechanical model for 3-phase magnetoelectric composites consisting of spherical magnetostrictive and piezoelectric particles embedded in a conductive polymer matrix. Based on their model, the authors calculated the magnetoelectric charge and voltage coefficients, and the results agreed reasonably well with corresponding experimental data.…”
Section: Introductionmentioning
confidence: 99%